ปัจจัยที่มีผลต่อการตัดสินใจเลือกสมาชิกสภาผู้แทนราษฎรของประชาชน : ศึกษากรณีการเลือกตั้งซ่อมสมาชิกสภาผู้แทนราษฎรจังหวัดนครพนม เขต 1 พ.ศ. 2537 - ศิวะพร ปัญจมาลา (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
This study is aimed at finding out factors contributing to making the electorates deciding to choose certain candidates in the by-election in the constituency number one of Nakhon Phanom province in 1994. Factors considered to be of significance are the party itself, the candidates, and the vote-canvassers. Seven hundred sampling cases in six districts and one sub-district are used. It can be concluded that the most significant factors affecting electorate’s decisions are the political party, the quality of the candidate, and the vote-canvassers respectively. From observations, it is known that people are fairly interested in this election.